Uma arquitetura de referência para projetar ferramentas de modernização baseadas em ADM - Santos, Bruno Marinho (Universidade Federal de São Carlos, 2023)
Software systems are constantly changing and this process generally makes it increasingly difficult for organizations to maintain. To help in this context, Object Management Group (OMG) proposed Architecture-Driven Modernization (ADM) that defends the realization of reengineering processes following the model-oriented architecture. One of ADM's main contributions is its sets of metamodels and its conceptual architecture. The construction of modernization tools that use the concepts of ADM have a greater chance of being interoperable. However, there are not many works in the literature that help in the construction of modernization tools based on ADM. Thus, the main objective of this Ph.D. research was to develop a Reference Architecture (RA) that supports the creation and evolution of modernization tools that are based on ADM's concepts and standards. The RA is formed by a set of diagrams representing architectural visions. For the creation of the RADM that is our Reference Architecture for ADM-based Modernization Tools, ProSA-RA was used, a process that systematizes the design, representation and evaluation of reference architectures. This Ph.D. research was evaluated through a questionnaire with ADM specialists (software developers and researchers) and software architects whose main objective was to obtain feedbacks on the acceptance of the Reference Architecture that was developed. The questionnaire that was applied brought as main results the following conclusions: (i) 100% of the participants agreed that the RA is clear and well described and (ii) 75% agreed that the RA is useful for create instances of different types of modernization tools.
A reference architecture for designing ADM-based modernization tools
Keywords: Architecture-driven modernization; Modernization tool; Reference architecture; Taxonomy; ProSA-RA; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO